2010
DOI: 10.1007/s10955-010-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Dynamics of the Curie-Weiss Model: Periodic Orbits, Multiple Histories, and Loss of Gibbsianness

Abstract: We consider the Curie-Weiss model at initial temperature 0 < β −1 ≤ ∞ in vanishing external field evolving under a Glauber spin-flip dynamics with temperature 0 < β −1 ≤ ∞. We study the limiting conditional probabilities and their continuity properties and discuss their set of points of discontinuity (bad points). We provide a complete analysis of the transition between Gibbsian and non-Gibbsian behavior as a function of time, extending earlier work for the case of independent spin-flip dynamics.For initial te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 23 publications
5
73
0
Order By: Relevance
“…The non-reversible time-evolutions we consider here suggest another set of questions, namely whether there are any non-Gibbsian pathologies along the trajectories depending on starting measures as found for reversible dynamics in [16,18,39,36,20,17,14,33,22]. Acknowledgement: This work is supported by the Sonderforschungsbereich SFB | TR12-Symmetries and Universality in Mesoscopic Systems.…”
Section: Ideas Of the Proofmentioning
confidence: 79%
“…The non-reversible time-evolutions we consider here suggest another set of questions, namely whether there are any non-Gibbsian pathologies along the trajectories depending on starting measures as found for reversible dynamics in [16,18,39,36,20,17,14,33,22]. Acknowledgement: This work is supported by the Sonderforschungsbereich SFB | TR12-Symmetries and Universality in Mesoscopic Systems.…”
Section: Ideas Of the Proofmentioning
confidence: 79%
“…In Fernández, den Hollander and Martínez [13], building on earlier work by Külske and Le Ny [15] and Ermolaev and Külske [12], we showed that this program can be fully carried out for the Curie-Weiss model subject to an infinite-temperature dynamics. The goal of the present paper is to extend this work away from the mean-field setting by considering a model with a Kac-type interaction, i.e., Ising spins with a long-range interaction.…”
Section: Motivation and Outlinementioning
confidence: 81%
“…Proof of Proposition 4.9. Considering the proof of Proposition 4.5, note that the estimates (10), (11) and (12) also hold at the critical time. In particular we still have supσ ω B ρ(ω C∩B ) ≤ 1.…”
Section: 1mentioning
confidence: 93%